In vitro comparison of one-step, two-step, and three-step polishing systems on the surface roughness and gloss of different resin composites - Lippert, Vinícius Funghetto; Bresciani, Eduardo [UNESP]; Mota, Eduardo Gonçalves; Bittencourt, Hélio Radke; Kramer, Paulo Floriani; Spohr, Ana Maria (Wiley, 2024)
Objectives: This laboratory study evaluated the effect of three polishing systems on the surface roughness and gloss of resin composites. Materials and Methods: Thirty specimens (6 mm Ø × 8 mm) were fabricated from each of three resin composites: Z 350 XT (nanofill), Harmonize (nanohybrid), and Estelite Omega (supranonofill). All specimens were photopolymerized using a multi-peak LED curing unit (VALO—Standard mode), having a exitance irradiance of approximately 1000 mW/cm2 against a polyester strip (PS). 2 mm was then removed from the irradiated end (finished) using #320 abrasive paper (F). Specimens were then randomly polished (P) using a one-step (1S) (OneGloss), two-step (2S) (EVE Diacomp Twist Basic CA), or 3-step (3S) (Astropol P) system (n = 10). For PS, F, and P groups, surface roughness (Ra) was measured using a surface roughness tester, and surface gloss was measured with a glossmeter. For each specimen, the percent recovery to the PS value (%R) of surface roughness and surface gloss were calculated. Data were analyzed using two–way ANOVA, followed by Tukey's test. Surface roughness and gloss values were submitted to Pearson's correlation test (α = 0.05). All statistical testing was performed using a pre-set alpha of 0.05. Results: The interaction term [resin composite × polishing system] was significant for both surface roughness (p = 0.001) and gloss (p = 0.0001). For all resin composites, the 2S and 3S systems provided a higher %R of surface roughness and gloss compared to those of the 1S system. There was a negative correlation between surface roughness and gloss, but only a few combinations showed strong correlations. Conclusions: The 2S and 3S polishing systems provided surfaces having greater smoothness and gloss compared to the 1S system. The ability to recover surface roughness and gloss was dependent on type of resin composite filler classification. Clinical Significance: The 3S and 2S polishing systems were more effective in achieving PS values than was the 1S system for all tested resin composites. However, individual polishing systems performed differently depending on type of resin composite.
Keywords: polishing system; resin composites; surface gloss; surface roughness